Phacoemulsification using a Chisel-Shaped Illuminator: Enhanced Depth Trench, One-Shot Crack, and Phaco Cut. Issue 3 (May 2016) - Wi, Jaemin; Seo, Hyejin; Lee, Jong Yeon; Nam, Dong Heun
Purpose: To evaluate the efficacy and outcomes of intracameral illuminator-assisted nucleofractis technique in cataract surgery. Methods: Since June 2012, this novel technique has been performed in all cataract cases by one surgeon (approximately 300 cases of various densities). Trenching continues until the posterior plate white reflex between an endonucleus and an epinucleus is identified (enhanced depth trench). After trenching, cracking is initiated with minimal separation force, and completion of cracking is confirmed by posterior capsule reflex (one-shot crack). With followability enhanced by an elliptical phaco mode, the divided nucleus is efficiently cut into small fragments by a chisel-shaped illuminator (phaco cut). Results: We have not experienced any capsular bag or zonular complications, and the effective phacoemulsification time seemed to be shorter than that with the conventional technique. Conclusions: This technique simplifies the complete division of the nucleus, which is the most challenging step in safe and efficient phacoemulsification.